Orchidopexy for Retractile Testes in Infertile Men: A Prospective Clinical Study - Dadfar, Mohammad Reza (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0; @font-face font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: Retractile testis may affect testicular parenchyma and spermatogenesis, and surgical treatment has been recommended for infertile men with retractile testes. We evaluated outcomes of orchidopexy in men with idiopathic infertility who suffered from bilateral retractile testes. Materials and Methods: We performed dartos pouch orchidopexy on 22 men with idiopathic infertility and bilateral retractile testes. The patients were subsequently followed up for 1 year and sperm parameters were assessed at 3-month intervals. Testicular volume was determined by ultrasonography 1 year postoperatively and compared with that before orchidopexy. Satisfaction with the appearance of the external genitalia, sexual desire, and the ability to have successful intercourse were assessed through a Likert-scale questionnaire. Results: Before the operation, the mean testicular volume was 12.2 Â± 5.0% lower than the lower normal limit of the testis volume in adults, and no clinically significant change was observed 1 year after the operation. Sperm density showed no significant changes postoperatively, but the mean proportion of sperms with high-grade motility witnessed a significant increase 1 year after the operation (P = .007). The mean percentage of sperms with normal morphology had a significant decrease at 1 postoperative year. Significant improvements were reported in satisfaction with the appearance of the external genitalia, sexual desire, and successful intercourse 1 year after the operation. Â Â Conclusion: Retractile testes might be at risk of growth retardation. We found that orchidopexy in retractile testes may improve sperm motility and increase fertility potential of the patients. We recommend orchidopexy in infertile men with bilateral retractile testes. Â